Effect of customer relationship Management on improving Financial Performance: An Applied Study in a Number of Iraq Private Banks (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The research focuses on determining the role of customer relationship management in improving financial performance by surveying the opinions of a number of employees of a number of Iraqi private banks. The customer has become the focus of attention and the most important factors of success and profitability and competition. Therefore, decisions related to the customer are important decisions that support the process of making, And follow-up of administrative decisions, including financial decisions aimed at improving the financial performance of banks and distinguish them from competitors.    Thus, the techniques used in customer relations management programs to collect, analyze and use data and information have become imperative for banks seeking to improve their financial performance better than competitors. The research reached a number of conclusions, the most important of which is the relationship and impact of customer relationship management on financial performance. The need to invest the best programs to manage customer relations and update constantly to keep abreast of developments.